A systematic literature review of social media for informal learning - Al-Sabaaw, Mohmed Y. M.; M. Dahlan, Halina; Zeki, Akram M. (University of Mosul, 2024)
Social media has become a valued platform to facilitate communication and informal learning for both individuals and organizations. Signiﬁcant attention to academic and professional ﬁelds attracts these trends. The rapid growth of research in social media for informal learning is increasing day by day. However, there are limited existing research studies that are found including the Systematic Literature Review (SLR), surveys, taxonomies, and simple reviews. SLR aims to deliver a comprehensive review and a better understanding of social media for informal learning. This study conducts an SLR to gather, analyze, and synthesize the data. Social media for informal learning SLR includes articles from different libraries. 114 primary studies are selected after the review and selection process for social media for informal learning. Further, we analyze and categorize the selected primary studies according to the various relevant research topics including the user’s behavior, beneﬁts, utilities, platform, tools for social media, and other topics. For this SLR, most of the reviewed studies focus on social media for informal learning users’ behaviour that highlight the research work in the future. The main objective of this SLR is to indicate the enhancement of informal learning with social media and give a new direction of research. The study comprehends the use of social media for informal learning and differentiates between informal learning and formal learning. This study highlights social media for informal learning in research activities with diverse conceptual lenses for informal learning research adopted by social media.